Pengenalan Literasi Keuangan dan Investasi Pasar Modal Syariah bagi Siswa SMA Negeri di Bawean - Shobri, Muwafiqus; Somad, Abdus; Alfiansyah, Rian (Journal of Smart Community Service, 2023)
The purpose of this activity is to teach students about financial literacy and investment in the Islamic capital market for students, the method used in this community service is to write and count while playing, the material consists of, getting to know (1) the history of money, (2) Islamic capital market (3) the ability to manage money wisely, (4) financial planning for future needs (5) the importance of the right investment. The activity was carried out at SMA Negeri 1 Sangkapura, Bawean, Gresik with 43 students participating. The results of the first day of service were that 23 participants were literate, then 8 participants were still less literate, and 12 participants did not have an understanding of financial literacy. Then after socialization, on the second day the service group held an evaluation and the result was that all participants understood how important it was to manage finances and use their pocket money wisely, why should they have savings, prioritize scales in using their money, then the participants also stated that they had tried to manage own finances.